Praññʻ thoṅʻ cu Mranʻ mā Nuiṅʻ ṅaṃ tuiṅʻʺ raṅʻʺ sāʺ yañʻ kyeʺ mhu ruiʺ rā dha leʹ thuṃʺ caṃ myāʺ (Mranʻ māʹ Chuirhayʻlacʻ Lamʻʺ cañʻ Pātī, Ba hui Koʻmītī Ṭhāna khyupʻ, 1967)
Social life and traditions of the ethnic groups of Burma.